Analisis Pengaruh Learning Organization dan Perceptions of Diversity Management Terhadap Employee Performance - Roland Sibuea; Yohana F. Cahya Palupi Meilani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The decline in employee performance at BUMN XYZ Company in Kotamobagu is hampering the achievement of company targets. This research aims to analyze the influence of learning organizations and perceptions of diversity management on employee performance, with job satisfaction and organizational commitment as mediation. The cross-sectional method was used with an online questionnaire filled out by 94 employees who had worked for at least one year. Data were analyzed using PLS-SEM. The results show a positive relationship between learning organization, perceptions of diversity management, job satisfaction, and organizational commitment on employee performance, but learning organization and job satisfaction are not significant. Organizational commitment mediates the relationship between perceptions of diversity management and employee performance, but does not mediate the relationship between learning organization. Managerial implications can help companies improve employee performance. This research has limitations and recommendations for further research.